2017
DOI: 10.18632/oncotarget.18307
|View full text |Cite
|
Sign up to set email alerts
|

Does the 1H-NMR plasma metabolome reflect the host-tumor interactions in human breast cancer?

Abstract: Breast cancer (BC) is the most common diagnosed cancer and the leading cause of cancer death in women worldwide. There is an obvious need for a better understanding of BC biology. Alterations in the serum metabolome of BC patients have been identified but their clinical significance remains elusive. We evaluated by 1H-Nuclear Magnetic Resonance (1H-NMR) spectroscopy, filtered plasma metabolome of 50 early (EBC) and 15 metastatic BC (MBC) patients. Using Principal Component Analysis, Partial Least-Squares Discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…Here, an orthogonalized partial least squares discriminant analysis model was built using data from 85 patients and validated in a cohort of 112 patients. A metabolic profile consisting of nine discriminant metabolites was established, but this profile was remarkably different from the one described by Richard et al The two studies had only one discriminant metabolite in common (pyruvate), but were in disagreement with respect to the level of pyruvate in metastatic versus early disease.…”
Section: Disease Characterization and Prediction Of Prognosismentioning
confidence: 80%
See 2 more Smart Citations
“…Here, an orthogonalized partial least squares discriminant analysis model was built using data from 85 patients and validated in a cohort of 112 patients. A metabolic profile consisting of nine discriminant metabolites was established, but this profile was remarkably different from the one described by Richard et al The two studies had only one discriminant metabolite in common (pyruvate), but were in disagreement with respect to the level of pyruvate in metastatic versus early disease.…”
Section: Disease Characterization and Prediction Of Prognosismentioning
confidence: 80%
“…In BCa, for example, the plasma metabolome has been found to discriminate between early‐stage and metastatic disease . Among the most important discriminant metabolites were lactate, glucose, and pyruvate.…”
Section: Disease Characterization and Prediction Of Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics is a relatively new -omics approach useful to study the complex and dynamic biochemical interplay occurring between cancer and host [13]. Thus, metabolomics not only can potentially identify the biochemical signals directly caused by the presence of cancer, but it can also detect the interaction between cancer and host, which is mainly mediated by the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…A significant part of this gluconeogenic glutamine comes from catabolism of muscle proteins, which reflects the correlation between cachexia and gluconeogenesis . Very recently, a study of plasma metabolome from breast cancer patients revealed a positive correlation between lactate, pyruvate, and alanine levels, and a negative correlation of pyruvate and alanine with glucose . This corresponds with the Cori cycle, an inter‐system cycle active in tumor patients: lactate released from cancer cells, but also from muscles, goes to the liver, as well as alanine from muscle, and these metabolites are used in gluconeogenesis in that organ, increasing the glucose available for cancer cells and their stroma, and thus enhancing tumor malignancy and associated body weight loss (Figure ) .…”
Section: Host Metabolism Alterations After Tumor Developmentmentioning
confidence: 99%